Application of Good Governance Principles in Land Registration Service in Parigi Moutong - Surahman; Wahid, Abdul; S., Irzha Friskanov; Anandy, Widyatmi (Alauddin Law Development Journal, 2024)
The purpose of this article is to determine and analyze the application of good governance principles in land registration services in Parigi Moutong Regency. The findings showed that the law that covers the land certificate policy states that land can be owned by people either alone or jointly with other people and legal entities. By using empirical juridical research methods and using the theory of the rule of law and general principles of good governance as well as identifying with legal and conceptual approaches. It is concluded that the implementation of good governance in the performance of land registration public services in Parigi Moutong based on regulations can be measured through the elements of productivity, responsiveness and accountability. The element of responsiveness to the implementation of BPN Parigi Moutong’s performance still has a less than optimal attitude towards parties applying for land permits.